2013
DOI: 10.1016/j.bpj.2013.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Mode-Specific Reorganization Energies and Ultrafast Solvation Dynamics of Tryptophan from Raman Line-Shape Analysis

Abstract: Tryptophan is widely used as an intrinsic fluorophore for studies of protein structure and dynamics. Its fluorescence is known to have two decay components with lifetimes of 0.5 and 3.1 ns. In this work we measure the ultrafast dynamics of Tryptophan at <100 fs through measurements and modeling of the Raman excitation profiles with time-dependent wave packet propagation theory. We use a Brownian oscillator model to simulate the water-tryptophan interaction. Upon photoexcitation to the higher singlet electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 50 publications
(89 reference statements)
3
14
0
Order By: Relevance
“…It is attributed to the vibronic coupling of these UVRR modes with nearby high energy electronic state, which is not involved in resonance enhancement of UVRR bands. These types of shifts in experimental REP's with respect to the absorption maximum are previously reported in tryptophan and 6‐chloroguanine molecules upon deep UV excitations. We have shown that there are two weak electronic transitions (one higher and one lower in energy) close to the electronic state centered at around 266 nm (see Figure b).…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…It is attributed to the vibronic coupling of these UVRR modes with nearby high energy electronic state, which is not involved in resonance enhancement of UVRR bands. These types of shifts in experimental REP's with respect to the absorption maximum are previously reported in tryptophan and 6‐chloroguanine molecules upon deep UV excitations. We have shown that there are two weak electronic transitions (one higher and one lower in energy) close to the electronic state centered at around 266 nm (see Figure b).…”
Section: Resultssupporting
confidence: 78%
“…The inertial solvent response time obtained in our simulation (26.5 fs) for RF and FMN is in the same order as earlier reports on 6‐chloroguanine (~15 fs) and tryptophan (~8 fs) . We have used same solvent correlation time (26.5 fs) for both the molecules, as we have shown in earlier reports that our model is not very sensitive to the timescale of dynamic solvent response …”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…26 But when the uorophore moves from the bulk aqueous phase to an organized assembly, its corresponding reorientation time slows down to 10 À9 second. So the difference in time scale affects the dynamics, and literature studies have indicated 27 that this could be related to the mode-specic reorganization of solvents. Hence there will be contributions from both the fast and inertial responses of solvent molecules which are manifested as summative to the change in the reorganization energy.…”
Section: Introductionmentioning
confidence: 99%